How to train professionals for managing the contradictions of a multiethnic society? - Loretta Fabbri; Claudio Melacarne (Freedom from Fear, 2020)
The society we live in is so diverse and mixed that we are no longer able to understand it only through traditional research perspectives. It is multiethnic and we often see that the stories shared in the public arena do not reflect what happens in everyday life.